Associations of long-term exposure to fine particle and its components with ischemic stroke: A cohort study in China - Lisha Xu; Yexiang Sun; Xinhan Zhang; Jingjing Hu; Jie Qiu; Yonghao Wu; Zongming Yang; Yixing Wang; Zihan Li; Jiayun Zhang; Ping Cheng; Dandan Xu; et al. (Ecotoxicology and Environmental Safety)
Background: Several studies have demonstrated that prolonged exposure to PM2.5 is associated with elevated risks of developing ischemic stroke (IS). However, evidence on the association of PM2.5 components with IS is still lacking. Thus, we aimed to estimate the association of 15 chemical components of PM2.5 with risk of IS in a cohort study. Methods: A community-based prospective cohort study comprising 29,926 participants was conducted in Yinzhou district, Ningbo, China. We utilized a land-use regression model to calculate the concentrations of PM2.5 and its 15 components. Adaptive elastic net (AENET) models were used to select important components from 135 predictors and environmental risk score (ERS) was calculated to quantify the multi-pollutant combined effect. Cox proportional hazard models and restricted cubic splines were used to estimate the associations of PM2.5 components with the occurrence of IS. Results: During 156,694 person-years of follow-up period, 770 new IS cases were identified. In single pollutant model, every IQR increased in PM2.5 (HR=1.240, 95 % CI: 1.098–1.401) and mercury (HR=1.441, 95 % CI: 1.240–1.675) was positively associated with risk of IS, whereas every IQR increased in cadmium (HR=0.935, 95 % CI: 0.900–0.971), antimony (HR=0.867, 95 % CI: 0.761–0.987), selenium (HR=0.700, 95 % CI: 0.611–0.802), and ammonium (HR=0.797, 95 % CI: 0.709–0.897) were inversely associated with IS. ERS was constructed by AENET according to 3 main effects (lead, selenium, and thallium), 3 square terms (beryllium, cadmium, and selenium), and 2 component-component interactions (beryllium × mercury and cadmium × selenium). A higher ERS was associated with a higher risk of IS (every IQR increased: HR=1.429, 95 % CI: 1.275–1.601). Conclusions: Long-term exposure to PM2.5 and its constituents may increase the risk of IS. Three heavy metals in PM2.5 from soil dust and coal combustion (lead, selenium, and cadmium), as well as three from non-ferrous metallurgy (thallium, beryllium, and mercury), contributed the most.